2018
DOI: 10.1088/1361-6382/aad70b
|View full text |Cite
|
Sign up to set email alerts
|

Charged black hole bombs in a Minkowski cavity

Abstract: Press and Teukolsky famously introduced the concept of a black hole bomb system: a scalar field scattering a Kerr black hole confined inside a mirror undergoes superradiant amplification that keeps repeating due to the reflecting boundary conditions at the mirror. A similar charged black hole bomb system exists if we have a charged scalar field propagating in a Reissner-Nordström black hole confined inside a box. We point out that scalar fields propagating in such a background are unstable not only to superrad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 73 publications
(284 reference statements)
5
61
0
1
Order By: Relevance
“…We discretize the field equations using a pseudospectral collocation grid on Gauss-Chebyshev-Lobbato points. The eigenvalues and respective eigenvectors are efficiently and accurately computed using a powerful numerical procedure developed in gravitational contexts in [45,46,[48][49][50][51][52][53][54][55][56][57][58][59][60] -discussed in detail in [56] and in section III.C and VI.A of the topical review [47] -which employs the Newton-Raphson root-finding algorithm. These numerical methods are very well tested in different contexts and extremely robust.…”
Section: Numerics: Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…We discretize the field equations using a pseudospectral collocation grid on Gauss-Chebyshev-Lobbato points. The eigenvalues and respective eigenvectors are efficiently and accurately computed using a powerful numerical procedure developed in gravitational contexts in [45,46,[48][49][50][51][52][53][54][55][56][57][58][59][60] -discussed in detail in [56] and in section III.C and VI.A of the topical review [47] -which employs the Newton-Raphson root-finding algorithm. These numerical methods are very well tested in different contexts and extremely robust.…”
Section: Numerics: Techniquementioning
confidence: 99%
“…These numerical methods are very well tested in different contexts and extremely robust. In particular, they are the same that were used to compute the ultraspinning and bar-mode gravitational instabilities of rapidly spinning Myers-Perry black holes [45,46,[48][49][50][51], the near-horizon scalar condensation and superradiant instabilities of black holes [52][53][54], the gravitational superradiant instability of Kerr-AdS black holes [55,56], the electro-gravitational quasinormal modes of the Kerr-Newman black holes [57] and the modes that violate strong cosmic censorship in de Sitter backgrounds [58][59][60], to mention a few. All our results have the exponential convergence on the number of gridpoints expected for a code that uses pseudospectral collocation (see [47]).…”
Section: Numerics: Techniquementioning
confidence: 99%
“…[10]. Working with solutions of given angular momentum, (9) reduces to a partial differential equation in 1 + 1-dimensions:…”
Section: Presentation Of the Numerical Strategymentioning
confidence: 99%
“…These charged black hole bombs have been somewhat less investigated than their rotating analogues but there is still a fair amount of studies, mostly numerical, available in the literature, for instance Ref. [4,8,9,14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In [24][25][26][27], boson stars and hairy black holes in a cavity were considered, and it showed that the phase structure of the gravity system in a cavity is strikingly similar to that of holographic superconductors in the AdS gravity. The stabilities of solitons, stars and black holes in a cavity were also studied in [28][29][30][31][32][33][34][35], which showed that the nonlinear dynamical evolution of a charged black hole in a cavity could end in a quasi-local hairy black hole. The thermodynamic behavior of de Sitter black holes in a cavity has been discussed in the extended phase space [36].…”
Section: Introductionmentioning
confidence: 99%